Habitual Fructose Intake Relates to Insulin Sensitivity and Fatty Liver Index in Recent-Onset Type 2 Diabetes Patients and Individuals without Diabetes. - Weber, KS; Simon, MC; Strassburger, K; Markgraf, DF; Buyken, Anette; Szendroedi, J; Müssig, K; Roden, M; Group, GDS (Nutrients)

Dietary carbohydrates: a review of international recommendations and the methods used to derive them. - Buyken, Anette; Mela, DJ; Dussort, P; Johnson, IT; Macdonald, IA; Stowell, JD; FJPH, Brouns (Eur J Clin Nutr)

FactCheck: Validating RDF Triples Using Textual Evidence - Habeeb Syed, Zafar; Röder, Michael; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 27th ACM International Conference on Information and Knowledge Management, CIKM 2018, Torino, Italy, October 22-26, 2018)

Discovering and Linking Spatio-Temporal Big Linked Data - Zinke, Christian; Ngonga Ngomo, Axel-Cyrille (2018 IEEE International Geoscience and Remote Sensing Symposium, IGARSS 2018, Valencia, Spain, July 22-27, 2018)

Caring, Cooking, Cleaning – repräsentative Zeitverwendungsmuster von Eltern in Paarbeziehungen - Klünder, Nina; Meier-Gräwe, Uta (Journal of Family Research)
As a result of the increasing labor force participation of mothers, this article questions how twoparent households divide the housework activities of caring, cooking and cleaning. Therefore three types of couples with different labor force participations were formed: Dual-earner couples, couples with additional female income and malebreadwinner couples. The time use for the mentioned activities was examined with a secondary analysis based on the German representative time use surveys of 2012/2013 and 2001/2002. The analysis showed that fulltime mothers spent the lowest amount of time for caring, cooking and cleaning. However, unemployed mothers spent the most time for these activities. Within a decade – from 2001/2002 to 2012/2013 – all mothers have reduced their time spent on household activities. Meanwhile, all parents in 2012/2013 take noticeably more time for child care. Regardless of the mother’s labor force participation, mothers still spent more time for caring, cooking and cleaning, especially on weekdays. Additionally, the everyday housework is divided by gender. Only on weekends, couples with employed mothers shared the care-work almost egalitarian.
Zusammenfassung
Vor dem Hintergrund der steigenden Erwerbstätigkeit von Müttern geht dieser Beitrag der Frage nach, wie Eltern in Paarbeziehungen die Haushaltsbereiche Betreuung, Beköstigung sowie Wohnungs- und Wäschereinigung untereinander aufteilen. Dazu werden drei Paartypen mit unterschiedlichem Erwerbsumfang gebildet: Zweiverdiener- Paare, Paare mit weiblichem Zuverdienst sowie Paare mit männlichem Familienernährer. Deren Zeitverwendung für die genannten Tätigkeiten wird mithilfe der repräsentativen Zeitverwendungserhebung 2012/2013 und 2001/2002 sekundäranalytisch untersucht. Die Analyse zeigt, dass vollzeiterwerbstätige Mütter täglich am wenigsten Zeit für die drei genannten Arbeitsbereiche im Haushalt aufwenden, nicht erwerbstätige Mütter hingegen am meisten. Innerhalb einer Dekade – von 2001/2002 bis 2012/2013 – haben alle untersuchten Mütter ihre Zeitverwendung für hauswirtschaftliche Tätigkeitsfelder reduziert, zeitgleich nehmen sich Eltern 2012/2013 deutlich mehr Zeit für Betreuungsaufgaben. Unabhängig des Erwerbsumfangs der Mutter ist die Arbeit des Alltags nach wie vor, besonders werktags, weiblich konnotiert und somit geschlechtsdifferenzierend aufgeteilt. Nur am Wochenende zeigt sich in Paaren mit erwerbstätiger Mutter bei der Betreuung eine annährend egalitäre Arbeitsteilung.

Zwischen selbst Gekochtem, Thermomix und Schulverpflegung – Innenansichten der Ernährungsversorgung von Familien mit erwerbstätigen Eltern - Klünder, Nina (Hauswirtschaft und Wissenschaft)

Relation of dietary glycemic index, glycemic load, added sugar intake, or fiber intake to the development of body composition between ages 2 and 7 y - Buyken, Anette; Cheng, Guo; Günther, Anke LB; Liese, Angela D; Remer, Thomas; Karaolis-Danckert, Nadina (The American Journal of Clinical Nutrition)

Flavonoid intake from fruit and vegetables during adolescence is prospectively associated with a favourable risk factor profile for type 2 diabetes in early adulthood - Penczynski, Katharina J.; Herder, Christian; Krupp, Danika; Rienks, Johanna; Egert, Sarah; Wudy, Stefan A.; Roden, Michael; Remer, Thomas; Buyken, Anette (European Journal of Nutrition)

New Method to Analyze the Throughput-Pressure Behavior with the Corrected Twin Screw Channel Geometry and the Induced Drag Flow of Screw Elements by Using 3D FEM Simulation - Schöppner, Volker; Sporkmann, F. (34th International Conference of the Polymer Processing Society (PPS))

Effect of Dietary Sugar Intake on Biomarkers of Subclinical Inflammation: A Systematic Review and Meta-Analysis of Intervention Studies - Della Corte, Karen; Perrar, Ines; Penczynski, Katharina; Schwingshackl, Lukas; Herder, Christian; Buyken, Anette (Nutrients)

The relevance of restrained eating behavior for circadian eating patterns in adolescents - Koch, Stefanie A. J.; Alexy, Ute; Diederichs, Tanja; Buyken, Anette; Roßbach, Sarah (PLOS ONE)

Dietary Patterns in Primary School are of Prospective Relevance for the Development of Body Composition in Two German Pediatric Populations - Wolters, Maike; Joslowski, Gesa; Plachta-Danielzik, Sandra; Standl, Marie; Müller, Manfred; Ahrens, Wolfgang; Buyken, Anette (Nutrients)
This study performed comparative analyses in two pediatric cohorts to identify dietary patterns during primary school years and examined their relevance to body composition development. Nutritional and anthropometric data at the beginning of primary school and two or four years later were available from 298 and 372 participants of IDEFICS-Germany (Identification and prevention of Dietary-induced and lifestyle-induced health Effects In Children and infants Study) and the KOPS (Kiel Obesity Prevention Study) cohort, respectively. Principal component analyses (PCA) and reduced rank regression (RRR) were used to identify dietary patterns at baseline and patterns of change in food group intake during primary school years. RRR extracted patterns explaining variations in changes in body mass index (BMI), fat mass index (FMI), and waist-to-height-ratio (WtHR). Associations between pattern adherence and excess gain in BMI, FMI, or WtHR (>75th percentile) during primary school years were examined using logistic regression. Among PCA patterns, only a change towards a more Mediterranean food choice during primary school years were associated with a favorable body composition development in IDEFICS-Germany (p < 0.05). In KOPS, RRR patterns characterized by a frequent consumption of fast foods or starchy carbohydrate foods were consistently associated with an excess gain in BMI and WtHR (all p < 0.005). In IDEFICS-Germany, excess gain in BMI, FMI, and WtHR were predicted by a frequent consumption of nuts, meat, and pizza at baseline and a decrease in the consumption frequency of protein sources and snack carbohydrates during primary school years (all p < 0.01). The study confirms an adverse impact of fast food consumption on body composition during primary school years. Combinations of protein and carbohydrate sources deserve further investigation.

Network meta-analysis reaches nutrition research - Schwingshackl, Lukas; Buyken, Anette; Chaimani, Anna (European Journal of Nutrition)

Association between full breastfeeding, timing of complementary food introduction, and iron status in infancy in Germany: results of a secondary analysis of a randomized trial - Libuda, Lars; Hilbig, Annett; Berber-Al-Tawil, Seda; Kalhoff, Hermann; Kersting, Mathilde (European Journal of Nutrition)

The role of genetic variation of human metabolism for BMI, mental traits and mental disorders - Hebebrand, Johannes; Peters, Triinu; Schijven, Dick; Hebebrand, Moritz; Grasemann, Corinna; Winkler, Thomas W.; Heid, Iris M.; Antel, Jochen; Föcker, Manuel; Tegeler, Lisa; Brauner, Lena; Adan, Roger A.H.; et al. (Molecular Metabolism)

Effect of an vitamin D deficiency on depressive symptoms in child and adolescent psychiatric patients – a randomized controlled trial: study protocol - Föcker, Manuel; Antel, Jochen; Grasemann, Corinna; Führer, Dagmar; Timmesfeld, Nina; Öztürk, Dana; Peters, Triinu; Hinney, Anke; Hebebrand, Johannes; Libuda, Lars (BMC Psychiatry)

Peer Learning im Lehramtsstudium – Praxisbeispiel einer diversitysensiblen Lernbegleitung im Fach Hauswirtschaft - Hellweg, Joanna (Peer Learning an Hochschulen. Element einer diversitysensiblen, inklusiven Bildung)

Konsum, Ernährung und Gesundheit als zentrale Handlungsfelder für die alltägliche Lebensführung - Schlegel-Matthies, Kirsten (Haushalt in Bildung und Forschung (HiBiFo))
Der Artikel diskutiert zunächst Ziele, Aufgaben und Anforderungen an alltägliche Lebensführung und -gestaltung. Im Anschluss werden vor allem Wechselbeziehungen zwischen Entwicklungen und Strukturen in Wirtschaft, Gesellschaft und Politik einerseits und individueller Lebensführung andererseits betrachtet.

Das Lernzentrum Ernährung, Konsum, Gesundheit (LEKG) - Schlegel-Matthies, Kirsten; Hellweg, Joanna (Heterogenität als Chance. Bilanz und Perspektiven des Qualitätspakt Lehreprojekts an der Universität Paderborn)

„Keine Zeit!?“ – Über den Umgang mit einer kostbaren Ressource - Raacke, Georg (Alltägliche Lebensführung im Zusammenspiel von Individuum und Gesellschaft)
Zeit ist eine wichtige Ressource. Viele Menschen haben oft das Gefühl, die Zeit renne ihnen davon. Dabei ist Zeit auch immer eingebunden in gesellschaftliche Praxis. Während in der Vormoderne die Natur maßgeblich für die Bestimmung der Zeit war, brachte die Erfindung der Uhr ein völlig anderes Verständnis von Zeit und entsprechend von Zeithandeln. Zeit wurde nicht mehr als zyklisch verstanden, sondern als linearer Ablauf von Ereignissen. Heute gilt nicht mehr ausschließlich die Zeit der Uhr, Menschen sollen vielmehr flexibel ihre Zeit nutzen. Das hat nicht zuletzt eine unmittelbare Bedeutung für die alltägliche Lebensführung.

Polygene Formen der Adipositas und Störungs-übergreifende Analysen - Giuranna, J.; Antel, J.; Libuda, Lars; Reinehr, T.; Peters, T.; Hebebrand, J.; Hinney, A. (Adipositas - Ursachen, Folgeerkrankungen, Therapie)
Zusammenfassung Neben monogenen Formen und Hauptgen-Effekten sind für die genetische Prädisposition zur Adipositas polygene Mechanismen relevant. Meta-Analysen von genom-weiten Assoziationsstudien (GWAMA) haben mehr als 700 polygene Loci oder Polygene identifiziert, die genom-weit mit dem Body Mass index (BMI) assoziiert sind. Diese prädisponierenden Genvarianten (Allele) finden sich bei adipösen Probanden häufiger als bei normalgewichtigen oder schlanken Individuen. Mittels statistischer Analysen wurden diese Allele als Adipositas-Risikoallele klassifiziert. Jede einzelne polygene Variante leistet nur einen kleinen Beitrag zur Entwicklung einer Adipositas und erhöht das Gewicht pro Risikoallel nur um ca. hundert Gramm bis 1,5 Kilogramm. Der Erfolg der GWAMA hat in letzter Zeit Phänotyp übergreifende, sogenannte Cross- Disorder- und Cross-Phänotyp-Analysen, ermöglicht. Dabei können Risiko-Gene identifiziert werden, die mittels Analysen der einzelnen Erkrankungen / Phänotypen nicht entdeckt werden konnten. Funktionelle Studien (in vitro und in vivo) der GWAMA-abgeleiteten Polygene können zu einem besseren Verständnis der Mechanismen der Körpergewichtsregulation führen.

Trinken – was und wie viel? - Hilbig, A.; Libuda, Lars; Kalhoff, H. (Kinder- und Jugendmedizin)
Zusammenfassung Wasser ist für Menschen das wichtigste Nahrungsmittel. Die Verfügbarkeit von ausreichend Trinkwasser in hoher Qualität hat große Bedeutung und ist weltweit ein herausforderndes Entwicklungsziel. Wasser hat im Körper viele Funktionen, etwa als Baustoff, Reaktionsmedium und Reaktionspartner oder als wichtiges Transportmedium. Ein gut regulierter Wasserhaushalt ist Voraussetzung für normale Körperfunktionen und für langfristige Gesundheit. Eine Dehydratation kann zu Symptomen wie Schwäche, niedrigem Blutdruck und Hypotonie führen und die Bewusstseinslage beeinträchtigen. Ein vollständiger Wasserentzug ist schon nach Tagen tödlich. Aber auch eine leichte Dehydratation beeinträchtigt langfristig die körperliche und geistige Leistungsfähigkeit. Angaben zum täglichen Wasserbedarf stützen sich vornehmlich auf epidemiologisch ermittelte Zufuhrdaten, die für gesunde Kinder und Jugendliche adäquat sind. Im Durchschnitt sollten Schulkinder etwa einen Liter und Jugendliche etwa 1,5 Liter täglich trinken. Zuckergesüßte Getränke mit hoher Energiedichte könnten das Risiko für Übergewicht und Adipositas erhöhen. Ein gesunder Getränkeverzehr kann mit Maßnahmen zur Verhaltensund zur Verhältnisprävention gefördert werden.

Effects of breastfeeding on health outcomes in childhood: beyond dose-response relations - Buyken, Anette; Karaolis-Danckert, Nadina; Günther, Anke; Kersting, Mathilde (The American Journal of Clinical Nutrition)

Habitual Flavonoid Intake from Fruit and Vegetables during Adolescence and Serum Lipid Levels in Early Adulthood: A Prospective Analysis - Penczynski, Katharina; Remer, Thomas; Herder, Christian; Kalhoff, Hermann; Rienks, Johanna; Markgraf, Daniel; Roden, Michael; Buyken, Anette (Nutrients)

In adolescence a higher ‘eveningness in energy intake’ is associated with higher total daily energy intake - Diederichs, Tanja; Perrar, Ines; Roßbach, Sarah; Alexy, Ute; Buyken, Anette (Appetite)

Positive Effects of Practical Nutrition Lessons in a Primary SchoolSetting with a High Proportion of Migrant School Children - Weber, Katharina S.; Eitner, Jessica; Dauben, Laura; Spörkel, Olaf; Strassburger, Klaus; Sommer, Jörn; Kaiser, Barbara; Buyken, Anette; Kronsbein, Peter; Müssig, Karsten (Experimental and Clinical Endocrinology & Diabetes)
Abstract Background Children with migration background are at increased risk for overweight, partly due to less favorable dietary habits compared to their German counterparts. We examined the effects of practical nutrition lessons among children with a high proportion of migration background in a primary school setting. Methods Ten 3rd and 4th grade classes (n=166 children, 73% with migration background) received the intervention and nine school classes (n=139 children, 76% with migration background) served as control. Before, shortly after (only among the intervention group) and three months after the three-day practical nutrition lessons, the nutrition-related skills, behavior, attitudes, and knowledge of the children were assessed using a questionnaire. Changes between baseline and 1st follow-up among children of the intervention group were calculated using linear mixed models. Differences between the two groups for changes between baseline and 2nd follow-up were tested using linear regression analyses. Models were adjusted for potential confounders. Results Shortly after the practical nutrition lessons, the children of the intervention group had improved their knowledge (β=1.7; 95% CI: 1.0; 2.4, P<0.001) and skills (β=1.8; 95% CI: 1.4; 2.2, P<0.001). These changes were sustainable and larger in the intervention compared to the control group (knowledge: β=1.6; 95% CI: 0.7; 2.5, P<0.001; skills: β=1.3; 95% CI: 0.7; 1.9, P<0.001). Changes in nutrition-related behavior and attitudes did not differ between the groups. Conclusions Providing practical nutrition lessons in a primary school setting with a high proportion of children with immigrational background improved the children’s nutrition-related knowledge and skills.

Time and age trends in morning and evening protein intakes of German children and adolescents - Roßbach, Sarah; Diederichs, Tanja; Herder, Christian; Buyken, Anette; Alexy, Ute (Journal of Nutritional Science)
Abstract The present study describes time and age trends in morning and evening protein intakes and sources among German children and adolescents from 1985 to 2014. A total of 9757 three-day weighed dietary records of 1246 3- to 18-year-old participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were analysed using polynomial mixed-effects regression models. Morning protein intake increased over the study period by approximately 1 % of morning energy intake (linear trend P < 0·0001), with the youngest and the oldest children having the highest protein intake (linear, quadratic trend P < 0·0001). Evening protein intake increased over time by approximately 2 % of evening energy intake in girls (linear trend P < 0·0001) and 1 % of evening energy intake in boys (quadratic trend P = 0·0313), with decreasing intake with age (girls: linear trend P < 0·0001; boys: linear trend P = 0·0963). Time trends were largely due to increases in protein from ‘starchy foods’. In conclusion, morning and evening protein intakes increased modestly between 1985 and 2014; these increases were, however, not accompanied by increases in traditional protein sources (i.e. meat or dairy products).

Surface structure evolution in a homologous series of ionic liquids - Haddad, Julia; Pontoni, Diego; Murphy, Bridget M.; Festersen, Sven; Runge, Benjamin; Magnussen, Olaf M.; Steinrück, Hans-Georg; Reichert, Harald; Ocko, Benjamin M.; Deutsch, Moshe (Proceedings of the National Academy of Sciences)
Interfaces of room temperature ionic liquids (RTILs) are important for both applications and basic science and are therefore intensely studied. However, the evolution of their interface structure with the cation’s alkyl chain length n from Coulomb to van der Waals interaction domination has not yet been studied for even a single broad homologous RTIL series. We present here such a study of the liquid–air interface for n=2to 22 , using angstrom-resolution X-ray methods. For n<6 , a typical “simple liquid” monotonic surface-normal electron density profile ρe(z) is obtained, like those of water and organic solvents. For n>6 , increasingly more pronounced nanoscale self-segregation of the molecules’ charged moieties and apolar chains yields surface layering with alternating regions of headgroups and chains. The layering decays into the bulk over a few, to a few tens, of nanometers. The layering periods and decay lengths, their linear n dependence, and slopes are discussed within two models, one with partial-chain interdigitation and the other with liquid-like chains. No surface-parallel long-range order is found within the surface layer. For n=22 , a different surface phase is observed above melting. Our results also impact general liquid-phase issues like supramolecular self-aggregation and bulk–surface structure relations.

Additive manufacturing for medical applications - Schramm, B.; Risse, L.; Brüggemann, J.P.; Richard, H.A.; Kullmer, G. (Journal of 3D Printing in medicine)

Crack Growth Simulation with Adapcrack3D in 3D Structures under the influence of Temperature - Joy, T.D.; Brüggemann, J.P.; Kullmer, G. (Procedia Structural Integrity)
results clearly demonstrate the great potential of additive

Internet of Things Canvas for Ideation in Model-Based Product Generation Planning - Albers, Alexander; Bernijazov, Ruslan; Kaiser, Lydia; Dumitrescu, Roman (IEEE - 13th System of Systems Engineering Conference, 19. - 22. Jun. 2018)

Real-time Graph-Based 3D Reconstruction of Sparse Feature Environments for Mobile Robot Applications - Gaspers, Daniel; Knorr, Christoph; Nickchen, Tobias; Nickchen, Daniel; Mertsching, Barbel; Mohamed, Mahmoud A. (2018 IEEE International Symposium on Safety, Security, and Rescue Robotics (SSRR))

Ti-6Al-4V alloy: 3D printing of lightweight implants and nanopatterning by self-assembly - Brassat, Katharina; Taube, A.; Kool, Daniel; Tasche, L.; Hoyer, K.P.; Schaper, Mirko; Lindner, Jörg

Eye-movement Modeling Examples in Source Code Comprehension: A Classroom Study - Bednarik, Roman; Schulte, Carsten; Budde, Lea; Heinemann, Birte; Vrzakova, Hana (Proceedings of the 18th Koli Calling International Conference on Computing Education Research, Koli, Finland, November 22-25, 2018)

Dietary Acid Load and Mental Health Outcomes in Children and Adolescents: Results from the GINIplus and LISA Birth Cohort Studies - Bühlmeier, Judith; Harris, Carla; Koletzko, Sibylle; Lehmann, Irina; Bauer, Carl-Peter; Schikowski, Tamara; von Berg, Andrea; Berdel, Dietrich; Heinrich, Joachim; Hebebrand, Johannes; Föcker, Manuel; Standl, Marie; et al. (Nutrients)

Tagungsbericht: Kulturen der Moral – Moral Cultures. Internationale und interdisziplinäre Tagung in Kooperation mit der DGEJ vom 19. bis 22. September 2018 an der Universität Paderborn. - Becker, Rieke; Heidgen, Michael; Lauert, Markus; Witschel, Verena

Design concept and prototype for an augmented reality based virtual preparation laboratory training in electrical engineering - Alptekin, Mesut; Temmen, Katrin (2018 IEEE Global Engineering Education Conference (EDUCON))
There have been numerous studies so far highlighting the potential of Augmented Reality (AR) in different educational domains and its impact on learners regarding their increased motivation, improved learning, concentration on the topic etc. Ever since high-end AR applications could be used on smartphones, this technology has become suitable to be used in many formal and informal learning environments and educational institutions, beginning with Arts courses in preschool over Biology, History, Chemistry, Physics etc. in K-12 and universities as well as in vocational schools ([1], [2]), e.g. for assembly trainings [3]. However, less research has been done regarding proper educational design principles and guides identifying the learning-promoting characteristics as to their efficacy in an AR environment ([1], [4]). Particularly there is a big lack for design concepts in the field of preparation and accompanying tools for laboratory work, since current studies are only extending real papers or books with additional links, videos or static 3D models (e.g. [5], [6]). Hence, this paper investigates and focuses at a design concept for mobile device based AR application (App) to acquire and deepen practical skills in dealing with electro-technical laboratory equipment and components. In a previous paper, the potentials and limitation of AR technology regarding engineering education with a special focus on laboratory work have been investigated to avoid common mistakes in the design concept.

Care und die Wissenschaft vom Haushalt

Hydrogen-bond supramolecular hydrogels as efficient precursors in the preparation of freestanding 3D carbonaceous architectures containing BCNO nanocrystals and exhibiting a high CO2/CH4 adsorption ratio - Lopez Salas, Nieves; Ferrer, M.L.; Gutiérrez, M.C.; Fierro, J.L.G.; Cuadrado-Collados, C.; Gandara-Loe, J.; Silvestre-Albero, J.; del Monte, F. (Carbon)
Keywords: General Chemistry; General Materials Science

3D-Risswachstum in homogenen, isotropen sowie funktional gradierten Strukturen - Dibblee, Katharina

Association between habitual coffee consumption and metabolic syndrome in type 1 diabetes - Stutz, Bianca; Ahola, A.J.; Harjutsalo, V.; Forsblom, C.; Groop, P.-H. (Nutrition, Metabolism and Cardiovascular Diseases)
Keywords: Cardiology and Cardiovascular Medicine; Nutrition and Dietetics; Endocrinology; Diabetes and Metabolism; Medicine (miscellaneous)

Bottom-up climate mitigation efforts - Kesternich, Martin

Grapherator: A Modular Multi-Step Graph Generator - Bossek, Jakob (Journal of Open Source Software)
Bossek, (2018). grapherator: A Modular Multi-Step Graph Generator. Journal of Open Source Software, 3(22), 528, https://doi.org/10.21105/joss.00528

Mixed Effects of Company-Initiated Customer Engagement on Customer Loyalty: The Contingency Role of Service Category Involvement - Steinhoff, Lena; Witte, C.; Eggert, A. (Journal of Service Management Research)

Wir sind jetzt alle Lernbegleiter“ – Nivellierungstendenzen in der multiprofessionellen Teamarbeit im Übergang Kita-Grundschule - Bührmann, Thorsten; Büker, Petra; Höke, Julia (Profession und Disziplin - Grundschulpädagogik im Diskurs. Jahrbuch Grundschulforschung. Band 22.)

Mahlzeitenmuster von Eltern in Paarbeziehungen - Klünder, Nina (Care und die Wissenschaft vom Haushalt)

Differenzierte Ermittlung des Gender Care Gap auf Basis der repräsentativen Zeitverwendungsdaten 2012/13 - Klünder, Nina

Essalltag und Arbeitsteilung von Eltern in Paarbeziehungen – Eine quantitative Analyse auf Basis der repräsentativen Zeitverwendungsdaten 2012/13 und 2001/02 - Klünder, Nina; Meier-Gräwe, Uta (Journal of Family Research)
The article examines the division of labor for everyday food routines of two-parent households depending on their labor force participation. Using data from the representative German Time Use Survey 2001/02 and 2012/13, three different pairs were formed: dual-earner couples, couples with additional female income and male-breadwinner couples Findings show that mother’s employment influences the time used for everyday food routines: It was found that the higher the employment rate of mothers, the less time was spent on food routine activities. Furthermore, the daily time used for everyday food routines was reduced from 2001/02 to 2012/13. The largest reductions were seen in the group of mothers working fulltime. Besides that, fathers were more engaged in meal preparation on the weekends, although the responsibility was the mother’s. In addition, the age and number of children in a household influenced the time used for everyday food routines. However, none of the examined pair constellations can help determine an egalitarian division of everyday food routines. There is still a labor division by gender.
Zusammenfassung
Der Beitrag untersucht die zeitliche Gestaltung sowie die innerfamiliale Arbeitsteilung des Essalltags von Müttern und Vätern in Paarbeziehungen differenziert nach deren Erwerbsumfang. Die Sekundäranalyse erfolgt auf Basis der repräsentativen Zeitverwendungsdaten 2012/13 und 2001/02, wobei drei Paarkonstellationen untersucht werden: Doppelverdiener-Paare, weibliche Zuverdiener- Paare sowie Paare mit männlichem Familienernährer. Die Analyse des Essalltags zeigt, dass der Erwerbsstatus der Mutter die zeitliche Gestaltung des Essalltags beeinflusst. Je höher dieser ist, desto weniger Zeit wird für die Ernährungsversorgung aufgewendet. Darüber hinaus hat sich die tägliche Zeitverwendung für die Ernährungsversorgung von 2001/02 bis 2012/13 reduziert, wobei die stärksten Einsparungen bei vollzeiterwerbstätigen Müttern zu konstatieren sind. Väter engagieren sich verstärkt am Wochenende bei der Mahlzeitenzubereitung, gleichwohl liegt die Verantwortung insgesamt bei den Müttern. Ebenso beeinflussen Alter und Anzahl der Kinder die Zeitverwendung für die Ernährungsversorgung. Letztlich kann in keiner untersuchten Paarkonstellation eine egalitäre Arbeitsteilung zur Gestaltung des Essalltags festgestellt werden. Vielmehr dominieren relativ ausgeprägte geschlechtsspezifische Arrangements.

Ausgewählte Ergebnisse der Zeitbudgeterhebungen 1991/92, 2001/02 und 2012/13 - Meier-Gräwe, Uta; Klünder, Nina (Familien stärken, Vielfalt ermöglichen. Bericht der familienpolitischen Kommission der Heinrich-Böll-Stiftung)

Generation Y. Wohin mit der Zeit? Ein empirischer Vergleich zur Zeitverwendung verschiedener Generationen - Zimmermann, Josepha; Klünder, Nina (Hauswirtschaft und Wissenschaft)

Carbohydrates from Sources with a Higher Glycemic Index during Adolescence: Is Evening Rather than Morning Intake Relevant for Risk Markers of Type 2 Diabetes in Young Adulthood? - Diederichs, Tanja; Herder, C; Roßbach, S; Roden, M; Wudy, SA; Nöthlings, U; Alexy, U; Buyken, Anette (Nutrients)

Hybrid coupled-mode modeling in 3D: perturbed and coupled channels, and waveguide crossings - Hammer, Manfred; Alhaddad, Samer; Förstner, Jens (Journal of the Optical Society of America B)
The 3D implementation of a hybrid analytical/numerical variant of the coupled-mode theory is discussed. Eigenmodes of the constituting dielectric channels are computed numerically. The frequency-domain coupled-mode models then combine these into fully vectorial approximations for the optical electromagnetic fields of the composite structure. Following a discretization of amplitude functions by 1D finite elements, pro- cedures from the realm of finite-element numerics are applied to establish systems of linear equations for the then- discrete modal amplitudes. Examples substantiate the functioning of the technique and allow for some numerical assessment. The full 3D simulations are highly efficient in memory consumption, moderately demanding in com- putational time, and, in regimes of low radiative losses, sufficiently accurate for practical design. Our results include the perturbation of guided modes by changes of the refractive indices, the interaction of waves in parallel, horizontally or vertically coupled straight waveguides, and a series of crossings of potentially overlapping channels with fairly arbitrary relative positions and orientations.
Keywords: tet_topic_waveguide; tet_topic_numerics

High protein intake along with paternal part-time employment is associated with higher body fat mass among girls from South China - Yang, Ming-zhe; Xue, Hong-mei; Pan, Jay; Libuda, Lars; Muckelbauer, Rebecca; Yang, Min; Quan, Liming; Cheng, Guo (European Journal of Nutrition)

Low 25(OH)-vitamin D concentrations are associated with emotional and behavioral problems in German children and adolescents - Husmann, Christiane; Frank, Mirjam; Schmidt, Börge; Jöckel, Karl-Heinz; Antel, Jochen; Reissner, Volker; Libuda, Lars; Hebebrand, Johannes; Föcker, Manuel (PLOS ONE)

Breastfeeding trends in healthy infants since 1990—results of the DONALD study - Libuda, Lars; Bolzenius, K; Alexy, U (European Journal of Clinical Nutrition)

Einzukaufen ist nicht schwer – Konsument zu sein dagegen sehr - Raacke, Georg (Haushalt in Bildung & Forschung)

Automatic Derivation of Geometric Properties of Components from 3D Polygon Models - Brandt, Sascha; Jähn, Claudius; Fischer, Matthias; Gerges, Maria; Berssenbrügge, Jan (Proceedings of the ASME 2017 International Design Engineering Technical Conferences & Computers and Information in Engineering Conference, Band 1)
To detect errors or find potential for improvement during the CAD-supported development of a complex technical system like modern industrial machines, the system's virtual prototype can be examined in virtual reality (VR) in the context of virtual design reviews. Besides exploring the static shape of the examined system, observing the machines' mechanics (e.g., motor-driven mechanisms) and transport routes for the material transport (e.g., via conveyor belts or chains, or rail-based transport systems) can play an equally important role in such a review. In practice it is often the case, that the relevant information about transport routes, or kinematic properties is either not consequently modeled in the CAD data or is lost during conversion processes. To significantly reduce the manual effort and costs for creating animations of the machines complex behavior with such limited input data for a design review, we present a set of algorithms to automatically determine geometrical properties of machine parts based only on their triangulated surfaces. The algorithms allow to detect the course of transport systems, the orientation of objects in 3d space, rotation axes of cylindrical objects and holes, the number of tooth of gears, as well as the tooth spacing of toothed racks. We implemented the algorithms in the VR system PADrend and applied them to animate virtual prototypes of real machines.

„Wer früher stirbt, ist selbst schuld!“ – Ein kritischer Blick auf das aktuelle Gesundheitsregime - Raacke, Georg (Haushalt in Bildung & Forschung)

Vitamin D and mental health in children and adolescents - Föcker, Manuel; Antel, Jochen; Ring, Stefanie; Hahn, Denise; Kanal, Özlem; Öztürk, Dana; Hebebrand, Johannes; Libuda, Lars (European Child & Adolescent Psychiatry)

Relevance of the dietary glycemic index, glycemic load and genetic predisposition for the glucose homeostasis of Chinese adults without diabetes - Cheng, Guo; Xue, Hongmei; Luo, Jiao; Jia, Hong; Zhang, Lishi; Dai, Junbiao; Buyken, Anette (Scientific Reports)

Relevance of chronotype for eating patterns in adolescents - Roßbach, Sarah; Diederichs, Tanja; Nöthlings, Ute; Buyken, Anette; Alexy, Ute (Chronobiology International)

Dietary Fatty Acids and Changes in Blood Lipids during Adolescence: The Role of Substituting Nutrient Intakes - Harris, Carla; Buyken, Anette; Koletzko, Sibylle; von Berg, Andrea; Berdel, Dietrich; Schikowski, Tamara; Koletzko, Berthold; Heinrich, Joachim; Standl, Marie (Nutrients)

Lower glycemic load meals reduce diurnal glycemic oscillations in women with risk factors for gestational diabetes - Kizirian, Nathalie V; Goletzke, Janina; Brodie, Shannon; Atkinson, Fiona S; Markovic, Tania P; Ross, Glynis P; Buyken, Anette; Brand-Miller, Jennie P (BMJ Open Diabetes Research & Care)

Positive Effects of Promoting Physical Activity and Balanced Diets in a Primary School Setting with a High Proportion of Migrant School Children - Weber, Katharina; Spörkel, Olaf; Mertens, Melina; Freese, Alem; Strassburger, Klaus; Kemper, Boris; Bachmann, Clemens; Diehlmann, Knut; Stemper, Theodor; Buyken, Anette; Ketelhut, Kerstin; Müssig, Karsten (Experimental and Clinical Endocrinology & Diabetes)
Abstract Background Children with migration background are at particular risk for overweight. We assessed the effects of a primary school-based initiative targeted at enhancing physical activity and dietary education among children with a high proportion of migration background. Methods Four 3rd and 4th grade classes (n=70 children, 77% with migration background) participated in a 10-months intervention comprising 2 additional exercise lessons weekly and 10 nutrition lessons per school year. 6 school classes (n=125 children, 65% with migration background) served as control. Before and after the intervention, an assessment of physical fitness and motor skills and questionnaires on dietary behavior and knowledge were conducted. In a subgroup (n=37), after 6 months of the intervention, daily physical activity was assessed by accelerometer-based monitoring. Differences in changes between the groups were assessed using linear regression analyses. Results Changes between the 2 time points for fitness and motor skill tests (differences in standard deviation scores) were larger in the intervention than in the control group for the total mean test value (β=0.38, p<0.001), driven by higher improvements in 5 of the 8 test items, i.e., obstacle race (speed) (β=0.22, p=0.049), standing long jump (strength) (β=0.35, p<0.001), sit-ups (strength) (β=0.33, p=0.002), stand and reach (mobility) (β=0.22, p=0.042), and 6 min run (endurance) (β=0.40, p<0.001), independently of confounders. Changes in dietary knowledge and consumption frequencies did not differ between groups. Conclusions Promoting guided physical activity in a primary school setting with a high proportion of children with migration background positively affected parameters of fitness and motor skills.

Entwicklung und additive Herstellung einer Leichtbau-Rotorwelle für eine permanentmagneterregte Synchronmaschine - Lammers, Stefan; Quattrone, Francesco; Mrozek, Rafael; Zimmer, Detmar; Schmid, Hans-Joachim; Ponick, Bernd; Hoffmann, Michael (Proceedings of the 14th Rapid.Tech Conference)
Additive Fertigungsverfahren (engl.: Additive Manufacturing, kurz: AM) ermöglichen die werkzeuglose Herstellung von Komponenten und kompletten Baugruppen direkt aus dem 3D-CAD-Modell. Insbesondere additiv hergestellte Leichtbaukonstruktionen weisen ein hohes Potential für den Elektromaschinenbau auf. In diesem Paper werden erste Ansätze zur additiven Fertigung einer Rotorwelle für eine permanentmagneterregte Synchronmaschine (PMSM) aufgezeigt. Die Verbesserung einer ausgeprägten Leichtbaukonstruktion der Rotorwelle sowie die Charakterisierung des additiv verarbeiteten Werkstoffs werden aufgeführt. Hierzu wurden Prüfkörper aus dem Werkstoffs H13 (1.2344) hergestellt. Des Weiteren wurden Prüfkörper additiv gefertigter Gitterstrukturen entwickelt und untersucht. Zur Werkstoffcharakterisierung wurden sowohl mechanische Eigenschaften ermittelt, wie die Streckgrenze, die Zugfestigkeit und die Härte als auch elektromagnetische Eigenschaften, wie die Koerzitivfeldstärke, die elektrische Leitfähigkeit und die Permeabilität. Die Ergebnisse zeigen, dass die magnetischen Eigenschaften von H13 durch eine angeschlossene Wärmebehandlung deutlich verbessert werden konnten. Im Anschluss an die Werkstoffcharakterisierung wurde ein innovatives Leichtbau-Rotorwellenkonzept mit internen Gitterstrukturen entwickelt. Verglichen mit einem konventionell gefertigten Rotor konnte die Rotormasse um 25% reduziert werden sowie das Massenträgheitsmoment um 23% reduziert werden bei einer Testdrehzahl von 3000 U/min und einem Drehmoment von 71,98 Nm.

Dimensional Tolerances for Additive Manufacturing: Fused Deposition Modeling - Knoop, Frederick; Lieneke, Tobias (Inside 3D Printing 2017)

Zn–VI quasiparticle gaps and optical spectra from many-body calculations - Riefer, Arthur; Weber, Nils; Mund, Johannes; Yakovlev, Dmitri R.; Bayer, Manfred; Schindlmayr, Arno; Meier, Cedrik; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)
The electronic band structures of hexagonal ZnO and cubic ZnS, ZnSe, and ZnTe compounds are determined within hybrid-density-functional theory and quasiparticle calculations. It is found that the band-edge energies calculated on the G0W0 (Zn chalcogenides) or GW (ZnO) level of theory agree well with experiment, while fully self-consistent QSGW calculations are required for the correct description of the Zn 3d bands. The quasiparticle band structures are used to calculate the linear response and second-harmonic-generation (SHG) spectra of the Zn–VI compounds. Excitonic effects in the optical absorption are accounted for within the Bethe–Salpeter approach. The calculated spectra are discussed in the context of previous experimental data and present SHG measurements for ZnO.

Assessing Genetic Algorithms for Placing Flow Processing-aware Control Applications - Auroux, Sébastien; Scholz, S.; Karl, Holger (Proc. European Wireless)

Evaluating the Influence of 3D-Printing Parameters on Acoustic Material Properties - Jäger, Axel; Johannesmann, Sarah; Claes, Leander; Webersen, Manuel; Henning, Bernd; Kupnik, Mario (2017 IEEE IUS~Proceedings)

Comparison of Conversion Efficiencies and Energy Yields of Micro-Inverters for Photovoltaic Modules - Krauter, Stefan (VDE-Proceedings of NEIS 2017 – Conference on Sustainable Energy Supply and Energy Storage Systems by IEEE-PES. Hamburg (Deutschland), 21.–22. September, 2017.)

Smart Charging Management System of Plugged-in EVs for Optimal Operation of Future Power Systems. - Krauter, Stefan; Ameli, Ali (VDE-Proceedings of NEIS 2017 – Conference on Sustainable Energy Supply and Energy Storage Systems by IEEE-PES. Hamburg (Deutschland), 21.–22. September, 2017.)

Analyse des Verformungsverhaltens von Übergangszonen partiell pressgehärteter Strukturen - Weiß Borkowski, Nathalie

Aspekte der Produktentwicklung in der additiven Fertigung - Ahlers, Dominik; Tröster, Thomas

Automatic Derivation of Geometric Properties of Components From 3D Polygon Models - Brandt, Sascha; Fischer, Matthias; Gerges, Maria; Jähn, Claudius; Berssenbrügge, Jan (Volume 1: 37th Computers and Information in Engineering Conference)
To detect errors or find potential for improvement during the CAD-supported development of a complex technical system like modern industrial machines, the system’s virtual prototype can be examined in virtual reality (VR) in the context of virtual design reviews. Besides exploring the static shape of the examined system, observing the machines’ mechanics (e.g., motor-driven mechanisms) and transport routes for the material transport (e.g., via conveyor belts or chains, or rail-based transport systems) can play an equally important role in such a review. In practice it is often the case, that the relevant information about transport routes, or kinematic properties is either not consequently modeled in the CAD data or is lost during conversion processes. To significantly reduce the manual effort and costs for creating animations of the machines complex behavior with such limited input data for a design review, we present a set of algorithms to automatically determine geometrical properties of machine parts based only on their triangulated surfaces. The algorithms allow to detect the course of transport systems, the orientation of objects in 3d space, rotation axes of cylindrical objects and holes, the number of tooth of gears, as well as the tooth spacing of toothed racks. We implemented the algorithms in the VR system PADrend and applied them to animate virtual prototypes of real machines.

Automatische Ableitung der Transportwege von Transportsystemen aus dem 3D-Polygonmodell - Brandt, Sascha; Fischer, Matthias (Wissenschaftsforum Intelligente Technische Systeme (WInTeSys) 2017)
In der CAD-unterstützten Entwicklung von technischen Systemen (Maschinen, Anlagen etc.) werden virtuelle Prototypen im Rahmen eines virtuellen Design-Reviews mit Hilfe eines VR-Systems gesamtheitlich betrachtet, um frühzeitig Fehler und Verbesserungsbedarf zu erkennen. Ein wichtiger Untersuchungsgegenstand ist dabei die Analyse von Transportwegen für den Materialtransport mittels Fließbändern, Förderketten oder schienenbasierten Transportsystemen. Diese Transportwege werden im VR-System animiert. Problematisch dabei ist, dass derartige Transportsysteme im zugrundeliegenden CAD-Modell in der Praxis oft nicht modelliert und nur exemplarisch angedeutet werden, da diese für die Konstruktion nicht relevant sind (z.B. der Fördergurt eines Förderbandes, oder die Kette einer Förderkette), oder die Informationen über den Verlauf bei der Konvertierung der Daten in das VR-System verloren gehen. Bei der Animation dieser Transportsysteme in einem VR-System muss der Transportweg also aufwändig, manuell nachgearbeitet werden. Das Ziel dieser Arbeit ist die Reduzierung des notwendigen manuellen Nachbearbeitungsaufwandes für das Design-Review durch eine automatische Berechnung der Animationspfade entlang eines Transportsystems. Es wird ein Algorithmus vorgestellt, der es ermöglicht mit nur geringem zeitlichem Benutzeraufwand den Animationspfad aus den reinen polygonalen dreidimensionalen Daten eines Transportsystems automatisch zu rekonstruieren.

Universal Micromachining Platform and Basic Technologies for the Manufacture and Marking of Microphysiological Systems - Moritzer, Elmar; Hirsch, André; Günther, K.; Sonntag, F.; Klotzbach, U.; Lasagni, A.F. (Micromachines)
Micro Physiological Systems (MPS), also known as Multi-Organ-Chip, Organ-on-a-Chip, or Body-on-a-Chip, are advanced microfluidic systems that allow the cultivation of different types of cells and tissue in just one common circuit. Furthermore, they thus can also adjust the interaction of these different tissues. Perspectival MPS will replace animal testing. For fast and flexible manufacturing and marking of MPS, a concept for a universal micromachining platform has been developed which provides the following latest key technologies: laser micro cutting of polymer foils, laser micro- and sub-micro-structuring of polymer foils, 3D printing of polymer components as well as optical inspection and online process control. The combination of different laser sources, processing optics, inspection systems, and print heads on multiple axes allows the change and exactly positioning to the workpiece during the process. Therewith, the realization of MPS including 3D printed components as well as direct laser interference patterned surfaces for well-defined cell adhesion and product protection is possible. Additional basic technologies for the generation of periodical line-like structures at polycarbonate foils using special Direct Laser Interference Patterning (DLIP) optics as well as for the 3D printing of fluid-tight cell culture reservoirs made of Acrylonitrile Butadiene Styrene directly onto polycarbonate microfluidics were established. A first prototype of the universal micromachining platform combining different lasers with Direct Laser Writing and DLIP is shown. With this laser micro cutting as well as laser micro-structuring of polycarbonate (PC) foils and therewith functionalization for MPS application could be successfully demonstrated.

Gemeinsam Mathematik lernen. Mit allen Kindern rechnen.

Ästhetisch-kulturelle Erfahrungsräume materialgestützten Schreibens - Rezat, Sara; Lehnen, Katrin (Ästhetische Erfahrungen – Theoretische Konzepte und empirische Befunde zur kulturellen Bildung. (Studien zur Germanistik und Anglistik, 22))

Bremseinrichtung für eine im unbetätigten Zustand eingefallene Bremse und entsprechende Aktoreinrichtung zum Lüften der Bremse - Zimmer, Detmar; Schadomsky, Magnus Hubert; Kriegel, Nils-Peter; Küter, Winfried; Neumann, Christopher
Die Erfindung betrifft eine Bremseinrichtung (12) für eine im unbetätigten Zustand eingefallene Bremse (10), wobei die Bremseinrichtung (12) eine Druckplatte (18), eine Gegenplatte (20), eine zum Verpressen einer Bremsscheibe (16) zwischen der Druckplatte (18) und der Gegenplatte (20) auf die Druckplatte (18) wirkende Energiespeichereinrichtung (22) sowie eine Lüftvorrichtung (26) zum Lüften der Bremse (10) aufweist, wobei diese Lüftvorrichtung (26) zum Lüften der Bremse (10) eine der Energiespeichereinrichtung (22) entgegenwirkende Aktoreinrichtung (28) aufweist. Es ist vorgesehen, dass die Lüftvorrichtung (26) weiterhin ein Getriebe (30) zur abschaltbaren Kraftübertragung der Kraft der Aktoreinrichtung (28) auf die Druckplatte (18) aufweist, wobei das Abschalten der Kraftübertragung über eine Schalteinrichtung (32) der Lüftvorrichtung (26) steuerbar ist. Die Erfindung betrifft weiterhin eine entsprechende im unbetätigten Zustand eingefallene Bremse (10).

Kosten und Nutzen Früher Hilfen. Eine lebensverlaufsbezogene Analyse - Wagenknecht, Inga

Kosten und Nutzen Früher Hilfen - Wagenknecht, Inga; Meier-Gräwe, Uta; Ziegenhain, Ute (Netzwerke in Frühen Hilfen und Gesundheitsförderung)

Building and Using an Ontology of Preference-Based Multiobjective Evolutionary Algorithms - Li, L; Yevseyeva, I; Basto-Fernandes, V; Trautmann, Heike; Jing, N; Emmerich, M (Evolutionary Multi-Criterion Optimization: 9$^th$ International Conference, EMO 2017, Münster, Germany, March 19-22, 2017, Proceedings)
Integrating user preferences in Evolutionary Multiobjective Optimization (EMO) is currently a prevalent research topic. There is a large variety of preference handling methods (originated from Multicriteria decision making, MCDM) and EMO methods, which have been combined in various ways. This paper proposes a Web Ontology Language (OWL) ontology to model and systematize the knowledge of preference-based multiobjective evolutionary algorithms (PMOEAs). Detailed procedure is given on how to build and use the ontology with the help of Protégé. Different use-cases, including training new learners, querying and reasoning are exemplified and show remarkable benefit for both EMO and MCDM communities.

Multi-objective Optimization for Liner Shipping Fleet Repositioning - Tierney, K; Handali, J; Grimme, C; Trautmann, Heike (Evolutionary Multi-Criterion Optimization: 9$^th$ International Conference, EMO 2017, Münster, Germany, March 19-22, 2017, Proceedings)
The liner shipping fleet repositioning problem (LSFRP) is a central optimization problem within the container shipping industry. Several approaches exist for solving this problem using exact and heuristic techniques, however all of them use a single objective function for determining an optimal solution. We propose a multi-objective approach based on a simulated annealing heuristic so that repositioning coordinators can better balance profit making with cost-savings and environmental sustainability. As the first multi-objective approach in the area of liner shipping routing, we show that giving more options to decision makers need not be costly. Indeed, our approach requires no extra runtime than a weighted objective heuristic and provides a rich set of solutions along the Pareto front.

Stack Overflow Considered Harmful? The Impact of Copy&Paste on Android Application Security - Fischer, Felix; Böttinger, Konstantin; Xiao, Huang; Stransky, Christian; Acar, Yasemin; Backes, Michael; Fahl, Sascha (2017 IEEE Symposium on Security and Privacy, SP 2017, San Jose, CA, USA, May 22-26, 2017)

Atomic and electronic structures evolution of the narrow band gap semiconductor Ag2Se under high pressure - Naumov, P; Barkalov, O; Mirhosseini, Hossein; Felser, C; A Medvedev, S (Journal of Physics: Condensed Matter)
Non-trivial electronic properties of silver telluride and other chalcogenides, such as the presence of a topological insulator state, electronic topological transitions, metallization, and the possible emergence of superconductivity under pressure have attracted attention in recent years. In this work, we studied the electronic properties of silver selenide (Ag2Se). We performed direct current electrical resistivity measurements, in situ Raman spectroscopy, and synchrotron x-ray diffraction accompanied by ab initio calculations to explore pressure-induced changes to the atomic and electronic structure of Ag2Se. The temperature dependence of the electrical resistivity was measured up to 30 GPa in the 4–300 K temperature interval. Resistivity data showed an unusual increase in the thermal energy gap of phase I, which is a semiconductor under ambient conditions. Recently, a similar effect was reported for the 3D topological insulator Bi2Se3. Raman spectroscopy studies revealed lattice instability in phase I indicated by the softening of observed vibrational modes with pressure. Our hybrid functional band structure calculations predicted that phase I of Ag2Se would be a narrow band gap semiconductor, in accordance with experimental results. At a pressure of ~7.5 GPa, Ag2Se underwent a structural transition to phase II with an orthorhombic Pnma structure. The temperature dependence of the resistivity of Ag2Se phase II demonstrated its metallic character. Ag2Se phase III, which is stable above 16.5 GPa, is also metallic according to the resistivity data. No indication of the superconducting transition is found above 4 K in the studied pressure range.

The Impact of Dietary Factors on Glycemic Control, Insulin Sensitivity and Secretion in the First Years after Diagnosis of Diabetes. - Weber, KS; Buyken, Anette; Nowotny, B; Strassburger, K; Simon, MC; Pacini, G; Szendroedi, J; Müssig, K; Roden, M; Group, GDS (Exp Clin Endocrinol Diabetes)

Associations between explorative dietary patterns and serum lipid levels and their interactions with ApoA5 and ApoE haplotype in patients with recently diagnosed type 2 diabetes. - Weber, KS; Knebel, B; Strassburger, K; Kotzka, J; Stehle, P; Szendroedi, J; Müssig, K; Buyken, Anette; Roden, M; Group, GDS (Cardiovasc Diabetol)

Exploring Term Networks for Semantic Search over RDF Knowledge Graphs - Marx, Edgard; Höffner, Konrad; Shekarpour, Saeedeh; Ngonga Ngomo, Axel-Cyrille; Lehmann, Jens; Auer, Sören (Metadata and Semantics Research - 10th International Conference, MTSR 2016, Göttingen, Germany, November 22-25, 2016, Proceedings)

Gleichstellung und innerfamiliale Arbeitsteilung. Mahlzeitenmuster und Beköstigungsarbeit in Familien im Zeitvergleich - Klünder, Nina; Meier-Gräwe, Uta (Wie die Zeit vergeht. Analysen zur Zeitverwendung in Deutschland. Beiträge zur Ergebniskonferenz der Zeitverwendungserhebung)

Glycaemic and insulin index of four common German breads - Goletzke, J; Atkinson, F S; Ek, K L; Bell, K; Brand-Miller, J C; Buyken, Anette (European Journal of Clinical Nutrition)

Commercial complementary food consumption is prospectively associated with added sugar intake in childhood - Foterek, Kristina; Buyken, Anette; Bolzenius, Katja; Hilbig, Annett; Nöthlings, Ute; Alexy, Ute (British Journal of Nutrition)
Abstract Given that commercial complementary food (CF) can contain high levels of added sugar, a high consumption may predispose to a preference for sweet taste later in life. This study examined cross-sectional associations between commercial CF consumption and added sugar intake in infancy as well as its prospective relation to added sugar intake in pre-school and primary-school age children. In all, 288 children of the Dortmund Nutritional and Anthropometric Longitudinally Designed Study with 3-d weighed dietary records at 0·5 and 0·75 (infancy), 3 and 4 (pre-school age) and 6 and 7 years of age (primary-school age) were included in this analysis. Individual commercial CF consumption as percentage of total commercial CF (%cCF) was averaged at 0·5 and 0·75 years. Individual total added sugar intake (g/d, energy percentage/d) was averaged for all three age groups. Multivariable logistic and linear regression models were used to analyse associations between %cCF and added sugar intake. In infancy, a higher %cCF was associated with odds for high added sugar intake from CF and for high total added sugar intake (>75th percentile, P <0·033). Prospectively, a higher %cCF was related to higher added sugar intake in both pre-school ( P <0·041) and primary-school age children ( P <0·039), although these associations were attenuated in models adjusting for added sugar intake in infancy. A higher %cCF in infancy may predispose to higher added sugar intake in later childhood by virtue of its added sugar content. Therefore, offering home-made CF or carefully chosen commercial CF without added sugar might be one strategy to reduce sugar intake in infancy and later on.

Age and time trends in eating frequency and duration of nightly fasting of German children and adolescents - Roßbach, Sarah; Diederichs, Tanja; Bolzenius, Katja; Herder, Christian; Buyken, Anette; Alexy, Ute (European Journal of Nutrition)

Prospective associations of meat consumption during childhood with measures of body composition during adolescence: results from the GINIplus and LISAplus birth cohorts. - Harris, C; Buyken, Anette; von Berg, A; Berdel, D; Lehmann, I; Hoffmann, B; Koletzko, S; Koletzko, B; Heinrich, J; Standl, M (Nutr J)

Oblique incidence of semi-guided waves on step-like folds in planar dielectric slabs: Lossless vertical interconnects in 3D integrated photonic circuits - Hildebrandt, Andre; Alhaddad, Samer; Hammer, Manfred; Förstner, Jens (Integrated Optics: Devices, Materials, and Technologies XX)
Keywords: tet_topic_waveguide

Fitness and fatness in relation with attention capacity in European adolescents: The HELENA study - Cadenas-Sanchez, Cristina; Vanhelst, Jeremy; Ruiz, Jonatan R.; Castillo-Gualda, Ruth; Libuda, Lars; Labayen, Idoia; De Miguel-Etayo, Pilar; Marcos, Ascensión; Molnár, Eszter; Catena, Andrés; Moreno, Luis A.; Sjöström, Michael; et al. (Journal of Science and Medicine in Sport)

Sedentary Behavior Is Independently Related to Fat Mass among Children and Adolescents in South China - Xue, Hongmei; Tian, Guo; Duan, Ruonan; Quan, Liming; Zhao, Li; Yang, Min; Libuda, Lars; Muckelbauer, Rebecca; Cheng, Guo (Nutrients)

Lunch at school and children’s cognitive functioning in the early afternoon: results from the Cognition Intervention Study Dortmund Continued (CoCo) - Schröder, Maike; Müller, Katrin; Falkenstein, Michael; Stehle, Peter; Kersting, Mathilde; Libuda, Lars (British Journal of Nutrition)
Abstract Studies about effects of school lunch on children’s cognition are rare; two previous studies (CogniDo, CogniDo PLUS) generally found no negative effects of lunch on children’s cognitive performance at the end of lunch break (i.e. 45 min after finishing lunch), but suggested potential beneficial effects for single parameters. Therefore, the present study investigated the hypothesis of potential positive effects of school lunch on cognitive performance at early afternoon (90 min after finishing lunch). A randomised, cross-over intervention trial was conducted at a comprehensive school with fifth and sixth grade students. Participants were randomised into two groups: On day 1, group 1 did not eat lunch, whereas group 2 received lunch ad libitum . On day 2 (1 week later), group 2 did not eat lunch and group 1 received lunch ad libitum . The cognitive parameters task switching, working memory updating and alertness were tested using a computerised test battery 90 min after finishing the meal. Of the 204 recruited children, fifty were excluded because of deviations from the study protocol or absence on one of the 2 test days, which resulted in 154 participants. Data showed no significant effects of lunch on task switching, working memory updating and alertness ( P values between 0·07 and 0·79). The present study suggests that school lunch does not seem to have beneficial effects on children’s cognitive functions regarding the conducted tests at early afternoon. Together with our previous studies, we conclude that school lunch in general has no negative effects on cognitive performance in children. However, beneficial effects seem to be restricted to a relatively short time period after eating lunch.

Changes in water and sugar-containing beverage consumption and body weight outcomes in children - Muckelbauer, Rebecca; Gortmaker, Steven L.; Libuda, Lars; Kersting, Mathilde; Clausen, Kerstin; Adelberger, Bettina; Müller-Nordhorn, Jacqueline (British Journal of Nutrition)
Abstract An intervention study showed that promoting water consumption in schoolchildren prevented overweight, but a mechanism linking water consumption to overweight was not substantiated. We investigated whether increased water consumption replaced sugar-containing beverages and whether changes in water or sugar-containing beverages influenced body weight outcomes. In a secondary analysis of the intervention study in Germany, we analysed combined longitudinal data from the intervention and control groups. Body weight and height were measured and beverage consumption was self-reported by a 24-h recall questionnaire at the beginning and end of the school year 2006/2007. The effect of a change in water consumption on change in sugar-containing beverage (soft drinks and juices) consumption, change in BMI (kg/m 2 ) and prevalence of overweight and obesity at follow-up was analysed using regression analyses. Of 3220 enroled children, 1987 children (mean age 8·3 ( sd 0·7) years) from thirty-two schools were analysed. Increased water consumption by 1 glass/d was associated with a reduced consumption of sugar-containing beverages by 0·12 glasses/d (95 % CI −0·16, −0·08) but was not associated with changes in BMI ( P =0·63). Increased consumption of sugar-containing beverages by 1 glass/d was associated with an increased BMI by 0·02 (95 % CI 0·00, 0·03) kg/m 2 and increased prevalence of obesity (OR 1·22; 95 % CI 1·04, 1·44) but not with overweight ( P =0·83). In conclusion, an increase in water consumption can replace sugar-containing beverages. As sugar-containing beverages were associated with weight gain, this replacement might explain the prevention of obesity through the promotion of water consumption.

Development of a Dietary Index to Assess Overall Diet Quality for Chinese School-Aged Children: The Chinese Children Dietary Index - Cheng, Guo; Duan, Ruonan; Kranz, Sibylle; Libuda, Lars; Zhang, Lishi (Journal of the Academy of Nutrition and Dietetics)

Organoblechnieten - Moritzer, Elmar; Budde, C.; Hüttner, M. (22. Nationales Symposium SAMPE (Society for the Advancement of Material and Process Engineering) Deutschland e.V.)